Questionnaire Survey on Public Perceptions on Temporary Housing and Prefabricated Temporary Houses: Focused on Stage-wise Acceptance and Personal Disposition - Bongchan Kim; Donggoo Seo; Taejun Yeom; Eunkyoung Hwang (Journal of the Korean Society of Hazard Mitigation, 2026)
Housing support for individuals displaced by disasters is typically provided in stages, from emergency shelters to temporary housing. Given the wide gap in living conditions between relief tents and prefabricated houses, the transitional space bridging them is critical but has received limited attention. This study analyzed public perceptions on stage-wise temporary housing through a survey, focusing on the role of a container-type private space as a transitional stage between tents and prefabricated houses. The results showed that the maximum acceptable duration of tent-living was a median of one week, which increased significantly to three weeks when an independent container-type private space was provided. The relationship between personal disposition and perceived habitability was significant at the tent stage but weakened after independent private space was secured. This confirms that a transitional private space can buffer the acceptance gap arising from individuals’ psychological characteristics. The standard unit for prefabricated houses was perceived as cramped. The bathroom was rated as the most important interior space, confirming the importance of private and sanitary areas. In sum, this study provides foundational data for establishing a stage-based temporary housing support system.